Refl ections about the job motivation and the human needs in the educational communities in the context of globalization - Cardona Echeverri, Diego Raúl (Pensando Psicología, 2010)
The sector of Education, as part of the social context, is immersed in the dynamics of globalization in the context of competitiveness. Here, change the forms of social organization, based on new subjectivities or ways to understand the world, in which requires new skills to meet the demands of the environment, inturn, are impel by the global market from permanent renewals, innovations and new technologies developments. Against this background of globalization, the educational communities are doomed to consider new directions within the competitiveness, as seek insight into their educational processes at the global level, of which note the new productive forces. Step opens to the crisis in Western socialization sys-tems, transformations imply rethink history and experiences of the various communities, specifi cally in the motivational conditions of which enable new representations that discuss the existing a worker with labour, stay for a few in which human capital becomes an employee of knowledge, their conditions are not favourable and do not guarantee their well-being and security.
Keywords: globalization; subjectivities; technologies developments; motivation; ducational processes